Advancements in English Language Teaching: Harnessing the Power of Artificial Intelligence - Umar, Umar (STIT Buntet Pesantren Cirebon, 2024)
The integration of Artificial Intelligence (AI) in English Language Teaching (ELT) represents a transformative shift in language education, offering innovative tools and approaches to enhance learning outcomes and experiences. This study explores the various AI technologies and applications employed in ELT, including personalized learning platforms, intelligent tutoring systems, automated writing evaluation tools, and language learning apps. Through a comprehensive review of existing literature, theoretical frameworks, and empirical studies, this paper examines the effectiveness, pedagogical implications, ethical considerations, and future directions of AI integration in ELT. Key findings reveal that AI-driven tools provide personalized, adaptive, and interactive learning experiences tailored to individual learners' needs, promoting student engagement, autonomy, and proficiency development. While AI technologies offer numerous benefits for language instruction, including improved learning outcomes, teacher efficiency, and accessibility, they also raise ethical and social considerations, such as data privacy, algorithmic bias, and equity issues. Addressing these challenges requires collaborative efforts among educators, policymakers, researchers, and technology developers to ensure responsible and equitable AI use in language education. Looking ahead, future directions include advancing AI technology, integrating AI and pedagogy, promoting ethical and responsible AI use, providing teacher training and professional development, fostering collaborative research and evaluation, innovating in assessment and evaluation, and promoting global collaboration and knowledge sharing in ELT. By embracing innovation, collaboration, and ethical practice, educators can harness the transformative power of AI technologies to create dynamic, inclusive, and effective language learning environments that empower learners to succeed in today's interconnected world.